COMPARISON OF MRI WITH DIAGNOSTIC KNEE ARTHROSCOPY FOR EVALUATING MENISCAL TEARS (Academia Science Repository, 2023)
This study compares the results of MRI and diagnostic arthroscopy of the knee joint to assess meniscal tears.